Vancomycin MIC as a predictor of outcome in MRSA bacteraemia in the UK context. - Hope, R; Blackburn, R; Verlander, N; Johnson, A; Kearns, A; Hill, R; Hopkins, S; Sheridan, E; Livermore, D (2013)
UNLABELLED: Received 29 November 2012; returned 20 February 2013; revised 16 May 2013; accepted 18 May 2013 OBJECTIVES: Raised vancomycin MICs have been associated with poor outcomes for methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia in the USA and mainland Europe. We investigated if this also applies in the UK, where EMRSA-15 (clonal complex 22) dominates. METHODS: Isolates from UK patients receiving vancomycin therapy for MRSA bacteraemia in 2008-10 were collected, along with clinical details. Outcomes (i.e. patient survival or bacteraemia resolution) were reported 28 days after vancomycin therapy ended. The relationship between clinical outcome and MIC--as determined by CLSI and BSAC agar dilution methods--was assessed. RESULTS: Among 228 MRSA bacteraemias, 82% were caused by EMRSA-15; 65% of the patients were male and the median age was 70.5 years. MICs correlated between methods, but CLSI agar dilution testing gave a mode at 1 mg/L with only 12% of results either side, whereas the BSAC method gave a mode straddling 0.7-1 mg/L with <4% outliers. Twenty-three percent of patients died, with MRSA contributory in half; another 17% had unresolved bacteraemia at 28 days. Neither death nor unresolved bacteraemia was significantly associated with higher vancomycin MICs by either method. Rifampicin co-therapy had no quantifiable effect on outcome. The patient's age was the only significant correlate of patient outcome (P < 0.01); the underlying medical condition of the patient was important for the resolution of bacteraemia (P < 0.01), though not for overall mortality. CONCLUSIONS: Subtle vancomycin MIC differences did not correlate with worse outcomes for vancomycin monotherapy or for vancomycin/rifampicin co-therapy in MRSA bacteraemia. Regardless of the exact MIC-outcome relationship, detecting such small MIC differences seems unlikely to be reliable in routine laboratories.